The schoolmasters - Fisher, Leonard Everett (Tarrytown, N.Y. : Benchmark Books, 1997)
Describes what education and the schools were like in colonial times
Originally published: New York : F. Watts, 1967
Includes index
Keywords: Teachers -- United States -- History -- Juvenile literature; Education -- United States -- History -- Juvenile literature; United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature